Análisis financiero en la cooperativa de ahorro y crédito san josé-airo ltda., de la parroquia el airo, cantón Espínola, provincia de Loja, periodos 2019-2020. - Jiménez Vélez, Lastenia Belén (2022)
The present curricular integration or degree work called: FINANCIAL ANALYSIS OF THE SAN JOSÉ-AIRO LTDA. SAVINGS AND CREDIT COOPERATIVE, OF THE EL AIRO PARISH, ESPÍNDOLA CANTON, LOJA PROVINCE, PERIODS 2019-2020., was carried out with the purpose of fulfilling the stated objectives and thus being able to know the economic and financial position of COAC San José-Airo Ltda., through the application of vertical analysis, horizontal analysis, and financial indicators. For this reason, in order to comply with the first specific objective, the vertical analysis and horizontal analysis were carried out, in order to determine the participation of each of the accounting accounts and the existing variations in the figures of their economic and financial structure, within assets, the group that has the greatest representativeness is Loan Portfolio, in 2019 with a total of $137,931.57, equivalent to 68.55% and in 2020 with a value of $153,668.03, which constitutes 67.10 % of total assets, due to the fact that it is an entity of the financial sector, it should be noted that in COAC San José-Airo Ltda., it only has a Credit Portfolio for Microenterprises. Within the liabilities, there are variations in the Regarding the economic structure, the income obtained was greater than the expenses, for the year 2019 they were $32,074.06 and for the year 2020 a total of $35,051.56, thus obtaining an increase of $2,977.50 equivalent to 9.28%; however, for 2020 the utility of the period was minimal . Next, financial indicators established by the SEPS were applied; The following results are pointed out: the cooperative has an important placement of its productive resources with an equivalent of 59.25%, however, their management can be further improved to reach optimal levels; In terms of delinquency, there was an equivalent to 29.75%, demonstrating a high rate of delinquency due to the fact that by 2020 there was growth in the past due portfolio; the problematic portfolio coverage is 40.40%, which is not enough to assume the uncollectible portfolio; In terms of liquidity, 56.15% is presented, evidencing that the cooperative has enough cash to meet its immediate obligations. As a last objective, the financial report was prepared, which will serve its directors as a tool in making decisions that go in the direction of improvement and maximization of profits, therefore, said report was prepared based on the results obtained mentioned above, Likewise, conclusions and recommendations were raised, these being possible solution alternatives aimed at managers and administrative staff.